Constructing meaning from cartoons: the effects of efl reading proficiency and working memory capacity on the processing of verbal and pictorial information - Woelfer, Sidnei Werner (2016)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2016